1994
DOI: 10.1002/pds.2630030406
|View full text |Cite
|
Sign up to set email alerts
|

Use of heparin for the prevention of venous thromboembolism

Abstract: The value of heparin in the prevention of venous thromboembolism has been shown effective and safe by controlled studies. However, how these studies have influenced physicians' decisions in thrombo‐prophylaxis is not known. With the aim of evaluating the frequency and the appropriateness of prophylaxis for venous thromboembolism in our centre, we performed a cross‐sectional study on a specific day. Among 667 patients who were admitted to hospital on this day, 134 (20 per cent) were receiving heparin. This had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We had previously documented an underuse of VTE prophylaxis before the institutional guideline was available [16,19] and an increased use of VTE prophylaxis two years after its implementation (unpublished data). A trend towards greater use of VTE prophylaxis is apparent during a ten-year period (table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously documented an underuse of VTE prophylaxis before the institutional guideline was available [16,19] and an increased use of VTE prophylaxis two years after its implementation (unpublished data). A trend towards greater use of VTE prophylaxis is apparent during a ten-year period (table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this scientific evidence, several studies have shown underuse of prophylaxis [15-18]. Previous studies carried out in our hospital on the use of deep vein thrombosis prophylaxis showed poor adherence to accepted recommendations [16,19]. The main problem was low use of prophylaxis in moderate/high risk patients.…”
Section: Introductionmentioning
confidence: 94%